Application for AI-OCR Module: Auto Detection of Emails/Letter Images - Fargas, Kelsey; Zhou, Bingjie; Staruk, Elizabeth; Tejada, Sheila (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
The purpose of this project is to provide instructions for teaching the Artificial Intelligence topic of supervised machine learning for the task of Optical Character Recognition (OCR) at various levels of a student’s undergraduate curriculum, such as basic knowledge, novice, and intermediate. The levels vary from beginner with a slight background in computing and computer science to intermediate with a better understanding of computer science fundamentals and algorithms.